2022
DOI: 10.3390/su14052781
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of International Trade on Sustainable Economic Growth: An Economic Policy Perspective

Abstract: This study uses the Gregory–Hansen cointegration method and the vector error correction model in the vector autoregression system to reveal how international trade contributes to economic sustainability. The Gregory–Hansen test for cointegration method reveals a permanent equilibrium relation among sustainably economic growth, exports, and imports and shows that exports facilitate GDP growth and accelerate improvements in the capability of imports in the long-run. The causality between GDP and exports is unidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(21 reference statements)
3
15
0
Order By: Relevance
“…The breakage of trade flows with Russia led to the danger of an energy crisis in Europe. All these events elucidated the interdependence of the countries and the importance of sustainable international trade for economic development [13]. However, trade sustainability depends on the sustainability of underlying factors, some of which exhibit increasing volatility.…”
Section: Introductionmentioning
confidence: 99%
“…The breakage of trade flows with Russia led to the danger of an energy crisis in Europe. All these events elucidated the interdependence of the countries and the importance of sustainable international trade for economic development [13]. However, trade sustainability depends on the sustainability of underlying factors, some of which exhibit increasing volatility.…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts to address the VAT Gap through economic growth also pose their own challenges. Economic growth (GDP growth) directs a country toward international trade (Ji et al, 2022;Rahman, 2021). International trade (Trade Openness) increases opportunities for tax violations due to the complexity and scale of trade transactions (Kitsios et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kang, I. et al proposed a model for evaluating affective policy performance, analyzed structural equation measurement data through structural equation modeling methodology, and revealed that policy implementation by firms is the most effective resource to encourage firms' international trade policy adoption [19]. Ji, X. et al used the gregoro -hansen fusion method and vector error correction model in vector auto-correction model to reveal how international trade contributes to the sustainability of the economy, showing that exporting contributes to GDP growth and accelerates the improvement of import capacity in the long run [20]. Yan, B. R. et al et al combined logistics risk influencing factors to establish the index system and evaluation model of international logistics risk [21].…”
Section: Introductionmentioning
confidence: 99%